Isolation and partial characterization of a human alveolar macrophage-derived neutrophil-activating factor. - Pennington, J E (1985)
Human alveolar macrophages (AM) were obtained from eight normal volunteers using fiberoptic bronchoscopic lavage to explore potential interrelationships among leukocytes in pulmonary defense against infection. AM placed in monolayer tissue cultures released material into culture supernatants with the capacity to enhance the bactericidal capacity of human neutrophils. Neutrophils preexposed to supernatants killed Pseudomonas aeruginosa from 70 to 90% more efficiently than control cells (P less than 0.02). AM culture supernatants contained this material by 4 h of incubation, and in vitro stimulation of AM cultures with heat-killed P. aeruginosa further increased its production. Gel filtration of AM culture supernatants with a G-50 Sephadex column allowed isolation of a 6,000-D neutrophil-activating factor (NAF) that was resistant to heat (56 degrees C, 30 min). The isoelectric point of NAF, as determined by chromatofocusing, was approximately 7.6. Enzyme digestion of NAF specimens, prepared sequentially by gel filtration and chromatofocusing, demonstrated 50-70% loss of activity after incubations with trypsin, chymotrypsin, and neuraminidase. NAF was only minimally chemotactic and eluted from Sephadex G-50 with particles of a different molecular size than those of AM-derived chemotactic factors (i.e., approximately 10,000 D and less than 500 D). Preincubation of neutrophils with NAF resulted in greater release of superoxide anion upon their subsequent stimulation by either bacterial phagocytosis or by phorbol myristate acetate, as compared with control neutrophils stimulated in a like manner. These studies indicate that human AM secrete a heat-stable, low molecular weight basic protein, with the capacity to enhance oxidative microbicidal activity of neutrophils.